2010
DOI: 10.1111/j.1439-0442.1975.tb01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Fatty Acid Composition of Sow's Colostrum and Milk Fat

Abstract: Summary Gas chromatographic analysis of 39 samples of colostrum and milk fat from 19 sows revealed 15 different fatty acids in all samples and trace amounts of three additional acids in some specimens obtained during the course of lactation. The changes in the fatty acid pattern occurring in the nursing period (7–10 days after farrowing) were characterized by a significant decrease in linoleic acid and an increase in palmitoleic acid. From the third week the total content of unsaturated acids showed a progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The current results were in agreement with the study conducted by Melichar, Ingr, and čErný, M., & Holub, A. () who reported that the proportion of C10:0, C12:0, C14:0 and C16:0 FAs was increased along with lactation time. C16:0 FA accounts for 25% to 35% of milk FAs, which is originally from sow blood and synthesized by mammary epithelial cells, and is the most important SFA in the sow milk (Lauridsen & Danielsen, ; Lv et al, ; Scow, Chernick, & Fleck, ; Tudisco et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The current results were in agreement with the study conducted by Melichar, Ingr, and čErný, M., & Holub, A. () who reported that the proportion of C10:0, C12:0, C14:0 and C16:0 FAs was increased along with lactation time. C16:0 FA accounts for 25% to 35% of milk FAs, which is originally from sow blood and synthesized by mammary epithelial cells, and is the most important SFA in the sow milk (Lauridsen & Danielsen, ; Lv et al, ; Scow, Chernick, & Fleck, ; Tudisco et al, ).…”
Section: Discussionsupporting
confidence: 93%